From Accessibility to Participation: The Strategy of the General Elections Commission (KPU) in Enhancing the Political Engagement of Persons with Disabilities in the 2024 Local Election in East Jakarta, Indonesia - Yoah Amiel, Boanerges; Wahidin, Danis Tri Saputra (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to analyze the strategies implemented by the General Election Commission (Komisi Pemilihan Umum-KPU) of East Jakarta in enhancing the political participation of persons with disabilities (PWDs) in the 2024 regional elections. This research addresses the persistent challenges faced by PWDs in accessing their political rights, particularly the low voter turnout despite a significant increase in their inclusion within the Permanent Voter List (Daftar Pemilih Tetap-DPT). Employing a qualitative approach with an explanatory case study design, the data were collected through in-depth interviews, direct observations, and document analysis involving KPU officials, disability organizations, and community stakeholders. The findings reveal that although the number of registered disabled voters in East Jakarta rose from 1,568 in 2017 to 17,502 in 2024, only 24% of them exercised their voting rights. Key obstacles include limited access to polling stations, insufficient voter education, and a lack of family and social support. However, several strategic innovations were found to be impactful, such as inclusive voter simulations, collaboration with disability organizations (e.g., PPUAD), social media-based outreach, and field-based data validation. The study contributes to electoral studies by highlighting the importance of dual strategies—offensive (proactive outreach and education) and defensive (protection and facilitation measures)—to empower marginalized voters. Moreover, the integration of digital platforms and community engagement models emerges as a key element for enhancing inclusive democratic participation. Compared to prior studies that primarily emphasized accessibility, this research brings an original focus on institutional collaboration, adaptive strategies, and the sociopolitical empowerment of PWDs within urban election systems. The findings underscore the need for continuous policy innovation and interagency cooperation to ensure meaningful participation of all citizens in democratic processes.